1996
DOI: 10.1002/j.1460-2075.1996.tb00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of tRNA-guanine transglycosylase: RNA modification by base exchange.

Abstract: tRNA‐guanine transglycosylases (TGT) are enzymes involved in the modification of the anticodon of tRNAs specific for Asn, Asp, His and Tyr, leading to the replacement of guanine‐34 at the wobble position by the hypermodified base queuine. In prokaryotes TGT catalyzes the exchange of guanine‐34 with the queuine (.)precursor 7‐aminomethyl‐7‐deazaguanine (preQ1). The crystal structure of TGT from Zymomonas mobilis was solved by multiple isomorphous replacement and refined to a crystallographic R‐factor of 19% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 42 publications
6
150
0
Order By: Relevance
“…Site-directed mutagenesis followed by biochemical characterization suggested four zinc ligands: cysteine 302, cysteine 304, cysteine 307, and histidine 317 [37]. The subsequent crystal structure of the TGT from Z. mobilis later confirmed that all three cysteine residues were coordinated to a zinc atom; however, the structure identified the fourth zinc ligand to be histidine 333 and not histidine 317 [19]. The role of the zinc atom appears to be in the maintenance of TGT structure and not in catalysis.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%
See 3 more Smart Citations
“…Site-directed mutagenesis followed by biochemical characterization suggested four zinc ligands: cysteine 302, cysteine 304, cysteine 307, and histidine 317 [37]. The subsequent crystal structure of the TGT from Z. mobilis later confirmed that all three cysteine residues were coordinated to a zinc atom; however, the structure identified the fourth zinc ligand to be histidine 333 and not histidine 317 [19]. The role of the zinc atom appears to be in the maintenance of TGT structure and not in catalysis.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%
“…The crystal structure of the TGT from Z. mobilis has been solved at 1.85 Å, revealing a non-canonical (β/α) 8 -barrel fold [18]. Soaking of the crystals with the preQ 1 substrate allowed for the first identification of the TGT active site [19]. Our laboratory, as well as others, has used this structure as the basis for mechanistic studies (Fig.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%
See 2 more Smart Citations
“…FIGURE 1. Deduced amino acid sequence of the trmD gene from S. typhimurium and alignment of all the known TrmD sequences obtained from the database using the box and shade program+ Numbers above the alignment correlate to amino acid positions in S. typhimurium and amino acid substitutions identified in different mutants are underlined+ Black shade indicates identical amino acids and gray shade indicate similar amino acids+ The stop codons are marked with asterisks+ The putative S-adenosyl methionine binding site is also underlined+ The Acinetobacter calcoaceticus trmD gene is only partially sequenced+ Translational starts of the trmD genes from the two Mycoplasma species are not identified+ (Romier et al+, 1996)+ Although the three-dimensional structure of enzyme-tRNA complex is required to fully understand in detail how a tRNA-modifying enzyme recognizes the tRNA substrate, identification of those amino acids that are influencing tRNA substrate specificity is a first step in such an analysis+ Such information will be valuable when the three-dimensional structure is known to identify which surface of the enzyme is engaged in the tRNA recognition+ As a first step to identify such amino acids in a tRNA-modifying enzyme, we have characterized mutant forms of the tRNA(m 1 G37)methyltransferase that do not methylate a structurally altered tRNA, but are still able to methylate its wild-type counterpart+…”
Section: Introductionmentioning
confidence: 99%